Fence. Volume 4, Rivals - Pacat, C. S. (Fence, 2020)
"Just as Nicholas, Seiji and the fencing team at the prodigious Kings Row private school seem to be coming together, a deadly rival from their past stands in their way once more. MacRobertson is the school that knocked Kings Row out of the State Championships last year - but unless Nicholas and Seiji can learn to work together as a team, their school is doomed once again! And maybe those two can learn to be something more than teammates..."--Back cover.